2023
DOI: 10.1017/mit.2023.39
|View full text |Cite
|
Sign up to set email alerts
|

Salvemini's antifascist exile in London: attracting the attention of a British audience

Abstract: In 1925 the Fascist dictatorship forced Gaetano Salvemini to leave Italy and begin a new life in exile. Salvemini understood he could find political and financial support in London to achieve two main aims: to live a decent life as an antifascist exile and fight the Fascist dictatorship from abroad. Thanks to a network encompassing intellectuals, academics, journalists, and politicians, London provided Salvemini with a platform for sharing antifascist stances outside Italy. This essay will develop research on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, the scholarship on Salveminieven as far as most recent studies are concernedis mostly written in Italian: not only does it remain confined within the linguistic borders of Italy, but it also denotes a dearth of international dissemination. To this day, only a handful of studies have been published and made accessible to an international readershipone in German, and the others in English (Bütler 1978;Killinger 2002 andTintori 2011, Tortarolo 2016Gussoni 2020a, Fantarella 2023. It seems relevant to summarise their content briefly.…”
Section: A Review Of the Scholarship On Salveminimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the scholarship on Salveminieven as far as most recent studies are concernedis mostly written in Italian: not only does it remain confined within the linguistic borders of Italy, but it also denotes a dearth of international dissemination. To this day, only a handful of studies have been published and made accessible to an international readershipone in German, and the others in English (Bütler 1978;Killinger 2002 andTintori 2011, Tortarolo 2016Gussoni 2020a, Fantarella 2023. It seems relevant to summarise their content briefly.…”
Section: A Review Of the Scholarship On Salveminimentioning
confidence: 99%
“…Exile is also relevant to Edoardo Tortarolo's study on Salvemini's historical method (2016): Tortarolo compares two methodological pieces completed in 1901 (Salvemini's inaugural lecture at the University of Messina) and in 1938 (a series of four lectures delivered at the University of Chicago, then published as Historian and Scientist), and concluded that, although Salvemini was exposed to the influence of US historical method, he did not radically change his approach. Salvemini's exile is the subject of two other works published in English in 2020 and 2022, by Alice Gussoni: the former (Gussoni 2020a) is a study of Salvemini's experience between Britain, France and the USA, shedding light on the transnational features of his exile; the latter is a biographical account which describes Salvemini's experience of mobility throughout his life, in Italy and abroad. Lastly, the most recent publication in English is a translation of Filomena Fantarella's (2023) study of Salvemini's relationship with his second wife, Fernande Dauriac, and particularly his stepson, Jean Luchaire, who collaborated with the Vichy government.…”
Section: A Review Of the Scholarship On Salveminimentioning
confidence: 99%